The Effects of DWI‐Infarct Lesion Volume on DWI‐FLAIR Mismatch: Is There a Need for Size Stratification?. Issue 4 (23rd November 2016) - Payabvash, Seyedmehdi; Taleb, Shayandokht; Benson, John C.; Rykken, Jeffrey B.; Oswood, Mark C.; McKinney, Alexander M.; Hoffman, Benjamin
ABSTRACT: BACKGROUND: The lack of fluid‐attenuated inversion‐recovery (FLAIR) hyperintensity in areas of diffusion‐weighted imaging (DWI) high signal, or DWI‐FLAIR mismatch, is a potential imaging biomarker for timing of stroke onset. We aimed to determine the effects of DWI infarct lesion volume on DWI‐FLAIR mismatch and its accuracy for identification of strokes within intravenous (IV) the thrombolytic therapy window. METHODS: Acute ischemic stroke patients with magnetic resonance imaging scan within 12 hours of witnessed stroke were included. Two neuroradiologists independently reviewed DWI and FLAIR sequences for DWI‐FLAIR mismatch in areas of restricted diffusion compared to the contralateral normal side. RESULTS: DWI‐FLAIR mismatch was identified in 21/82 (26%) patients. Infarct lesions with DWI‐FLAIR mismatch were scanned earlier (3.8 ± .3 vs. 7.5 ± .3 hours from onset, P < .001) and were smaller in size (8.9±2.3 vs. 43.1±11.9 mL, P = .007) compared to lesions without mismatch. Multivariate regression analysis showed a significant interaction between lesion volume and time‐from‐onset in relationship with the presence of DWI‐FLAIR mismatch ( P = .045). The presence of DWI‐FLAIR mismatch had 56% sensitivity, 83% specificity, 48% positive predictive value (PPV), and 87% negative predictive value (NPV) for identification of infarction within 4.5 hours of symptom onset; while for infarct lesions >15 mL, the DWI‐FLAIR mismatch had 100% specificity and PPV for acute infarcts within 4.5 hours of onset. CONCLUSION: The effects of stroke onset‐to‐scan time gap on DWI‐FLAIR mismatch are not the same for different DWI lesion volumes. At DWI lesion volumes >15 mL, the DWI‐FLAIR mismatch is highly specific for acute infarcts within IV thrombolytic therapy time, and can identify wake‐up stroke patients eligible for treatment.